Catanionic reverse micelles as an optimal microenvironment to alter the water electron donor capacity in a SN2 reaction - Villa, Cristian C. (2019)
The effect of interfacial water entrapped in two types of catanionic reverse micelles (RMs) on the kinetic parameters of the SN2 reaction between dimethyl-4-nitrophenylsulfonium trifluoromethanesulfonate (S+) and n-butylamine (BuNH2) was explored. Two catanionic surfactants, composed of a mixture of oppositely charged ionic surfactants without their original counterions, were used to create the RMs. Thus, benzyl-n-hexadecyldimethylammonium 1,4-bis(2-ethylhexyl) sulfosuccinate (BHD-AOT) and cetyltrimethylammonium 1,4-bis(2-ethylhexyl) sulfosuccinate (CTA-AOT) were formed. Also, the well-known anionic surfactant sodium 1,4-bis(2-ethylhexyl) sulfosuccinate (Na-AOT) was employed as a comparison. Our results showed an important catalytic-like effect of all RMs investigated in comparison with a water-benzene mixture, and the rate constant values depend on the type of surfactant used. Faster reaction in BHD-AOT RMs than in CTA-AOT and Na-AOT RMs was observed. This behavior was attributed to the strong interaction (by hydrogen bonding with AOT anion and ion-dipole interaction with BHD+) between the entrapped water and the BHD-AOT interface, which reduces the solvation capacity of water on S+. In CTA-AOT (and Na-AOT) RMs, the water-interface interaction is weaker and the electron pairs of water can solvate S+ ions. In summary, the chemical structure of the counterion on the catanionic surfactant alters the interfacial region, allowing the progress of a reaction inside the RMs to be controlled. ©